Cosplayers no Brasil: o surgimento de uma nova identidade social na cultura de massas - Coelho Junior, Leconte de Lisle (2008)
This study aims at focusing on the social identity of a group of cosplayers in the brazilian state of Espírito Santo. Cosplayers are transvestites that wear gowns typical of the characters found in mangás (Japanese cartoon magazines), and animes (caricatures in several games of nipponese origin). This practice has been supported by the japanese popular culture inserted into the state’s social environment. The sample counted on 12 informers, in an average medium of 18,66 years of age (DP = 1,44). The main results show that there is a great tendency in creating cosplayers that come from the nipponese media in detriment of others. These chosen character’s chief psychological traits apparently maintain some advantage over other aspects when people decide upon a certain characterization. Finally, these people feel themselves as creators of a social group that is based on two structural interactive categories: “Performance” and “Diversion”, which can be considered as typical of the entertainment mass culture society.